HISTORICAL BACKGROUND VERSUS STATED PREFERENCES - Baidoo, Isaac K.; Nyarko, Eric; Boadum, Gad Kusi (European Scientific Journal, ESJ, 2015)
The geographical imbalance of public sector teachers is one of the main challenges facing policy makers in developing countries. This study sought to analyze public sector teachers’ decision in choosing a remote and/or rural area job with reference to their historical background. Discrete choice experiment modeling approach was adopted to estimate consideration sets. The survey focused on 120 teacher trainees. The effects of certain attributes based on the findings from the study revealed that teachers were will to trade off location for benefits such as granting of study leave with pay, provision of housing, and early promotion (after 3 years of work). Teachers with rural living experience tended to prefer rural assignments. The extent to which teachers were will to trade off their initial preferences for salary was limited.